An Iterative Approach towards Single stage Axial Fan Design using Off Design Prediction - Arora, Rajat; Sundararaj, Ramraj H; Kushari, Abhijit (Defence Science Journal, 2021)
A single-stage axial fan having a pressure ratio of 1.01 is designed in the current study. The design pressure ratio is chosen based on the power available from the existing motor (2.2 kW). The design space for the axial flow fan was generated by varying specific flow and geometrical parameters in suitable steps, using a program written in MATLAB. The varied flow parameters are mass flow rate, inlet Mach number, inlet flow angle, and rotor speed. The geometrical parameters that were varied are hub to tip ratio, aspect ratio, and blade solidity. Using these as the input variables and applying free vortex theory for 3-dimensional blade design, the aerodynamic design of the axial flow fan was carried out. Performance parameters like flow coefficient, stage loading coefficient, degree of reaction, diffusion factor, De Haller’s number, and blade angles were calculated at the blade’s hub, mean, and tip. Total design space of 92160 data points was obtained from the combination of input parameters. Several constraints were applied to optimise the design space based on the available power from the existing motor and in-house manufacturing limitations. The initial design space was reduced to 82 data points using these constraints. To further reduce the number of points in the design space, off-design performance was evaluated for each of these data points. Following this, one design point was selected based on the optimum performance range in off-design operation, while considering manufacturing limitations. Using Mellor charts, a suitable blade profile was chosen based on the inlet and exit blade angles. NACA 65-410 airfoil was selected with a stagger of 55 degrees and an incidence of 6 degrees for optimum performance.